A framework for conceptualizing integrated prescriptive maintenance and production planning and control models - Kevin Wesendrup; Bernd Hellingrath; Zoi Nikolarakis (Brazilian Journal of Operations & Production Management)
Goal: This study aims to support researchers and managers in conceptualising new integrated prescriptive maintenance (PxM) and production planning and control (PPC) models.